Wind-induced vibration control of super-tall buildings using a new combined structural system. Issue 172 (January 2018) - Kalehsar, Houshyar Eimani; Khodaie, Nahmat
Abstract: The excessive vibration due to wind loads is the main concern in design and construction of super-tall buildings. The present paper proposes a new structural system to reduce the wind-induced vibrations of super-tall buildings. The proposed structural system is a combination of an exterior tubular structure and an interior or core structure, and consists of two upper and lower parts. At the upper part, the exterior and core structures are isolated from each other. Damping devices are used in this part to limit the relative flexural motion between the exterior and core structures and control the wind-induced motions of the building by dissipating the vibration energy. In order to demonstrate the control effectiveness of the proposed structure, a numerical example of a super-tall building is presented, and the along-wind and crosswind responses are obtained using the frequency domain analysis of multi-degrees-of-freedom lumped mass models. The control performance of the proposed system is compared with that of the structure controlled by the tuned-mass-damper (TMD) system. The results demonstrate that the proposed control structure, which is a self-control structural system, can effectively reduce the wind-induced vibrations of super-tall buildings and improve occupant comfort during strong wind excitation.